The price is right: making workplace wellness financially sustainable - Lee, S.; Blake, Holly; Lloyd, S. (Emerald, 2010)
Purpose – The public health argument for developing and maintaining workplace wellness programmes in organisations is well‐documented, particularly within the healthcare sector which aims to “set the example” for workplace health. However, workplace wellness also makes good business sense, since it is established that investing in employee health can reduce absenteeism, improve job satisfaction and productivity and enhance corporate image. Organisations often place workplace wellness low in their priorities. The purpose of this paper is to present the case for an initial resource investment and top‐level support to pump‐prime a financially sustainable, and even profitable, programme.